Tracing China's external driving sources and internal emission hotspots of export-driven PM10 emission. (20th April 2020) - Yuan, Ye; Chuai, Xiaowei; Zhao, Rongqin; Lu, Qinli; Huang, Xianjin; Xiang, Changzhao; Yuan, Xiaolan; Gao, Runyi; Lu, Yue; Huang, Xianyang; Guo, Xiaomin; Zhuang, Qizhi
Abstract: External trade could induce extensive air pollutant emissions among partners. PM10 (particles smaller than 10 μm) is an important pollutant that could cause various problems. Few studies have researched the spatial heterogeneity of this export-driven pollutant at a high physical spatial resolution, especially given the lack of detailed spatial data based on sectors. Based on the Eora and EDGAR databases, and the MRIO model, this study calculated the export pulled emissions, identified the external driving sources of China's PM10 emissions, visualized the actual internal export-driven PM10 emissions sources and hot spots at a high spatial resolution. China's export-driven and net export-driven PM10 emissions during 1990–2015 generally increased and decreased, respectively, and the net one reversed from positive to negative in 2012. Globally, the external driving sources of China's export-driven PM10 emissions were mostly Latin American and African developing countries/regions and other European developed countries/regions. Nationally, China's export-driven PM10 emissions were mainly from the emission-intensive secondary industries, and the whole emission decreased from southeast to northwest spatially. Emissions hot spots were mostly concentrated on the North China Plain, the Yangtze River Delta, the Pearl River Delta and the Sichuan Basin, and they exhibited a polarization phenomenon during 1990–2012. We finally proposed an importer-exporter shared responsibility mechanism to reduce export-driven PM10 emission. These results offer excellent references for China's government to enact targeted export-driven PM10 emissions mitigation strategies. Highlights: China's export-driven PM10 emission were mostly driven by developing countries/regions. China's export-driven PM10 emission distribution was highly coupled with that of its population. Export-driven emissions were mostly triggered by the secondary industry. Emission hot spots exhibited a polarization phenomenon and concentrated mostly on provincial capital. An importer-exporter shared responsibility mechanism was proposed.